Kecenderungan Depresi pada Pasien Lansia Rawat Inap COVID-19 Survivor menggunakan GDS-15 - Soenarti, Sri; Pradipto, Wiryawan (Jurnal Klinik dan Riset Kesehatan, 2021)
Background: The spreading of the Severe Acute Respiratory Syndrome Coronavirus (COVID-19) pandemic could be associated with psychiatric implications, including depression, one of the most common mental disorders. It is up-surging worldwide amid the ongoing coronavirus disease 2019 (COVID-19) pandemic, especially among hospitalized elderly COVID-19 survivors. Aim: To determine the impact of the COVID-19 pandemic on the possibility of depression using Geriatric Depression Scale-15 (GDS-15) questionnaire in hospitalized elderly COVID-19 survivors Methods: The study was an observational study with cross-sectional data collecting. We collected the subject of the study from elderly COVID-19 survivors hospitalized in Saiful Anwar General Hospital. Subjects were called by phone, and then they were asked based on the GDS-15 questionnaire. The questionnaires included demographic and socioeconomic data, health status, and GDS-15 score. Results: Among the 33 sample of this research, cross-sectional phoned surveys indicated that the elderly <70 years old were less psychologically distressed (p 0,057). The length of stay had a positive correlation with the GDS-15 score( p 0,157 ) Conclusion: Elderly COVID-19 survivors >70 years old tend to have possibility depression than <70 years old. A longer stay is correlated with the possibility of depression in elderly COVID-19 survivors. Occupation has a significant correlation with age that can affect the likelihood of depression.